Business Strategies in a Turbulent Business Environment: Findings from Indonesian Telecommunication Industry - Nashiruddin, Muhammad Imam (Jurnal Pekommas, 2019)
This study aimed to explore the development of business strategies in a turbulent business environment. The study involved leaders of several telecommunication business units in Indonesia as research respondents. The research used the descriptive and the explanatory survey method using Partial Least Square-Path Modeling (PLS-PM). The results showed that although the business strategies of the telecommunication companies in Indonesia were included in the good category; however, they were still not optimal because were mostly created through competitive strategy. Whereas, the cooperative strategy turned out to have a more dominant contribution to create superior competitive advantage in a turbulent business environment. The study also discussed problem solving on how the companies should formulate the business strategy in a turbulent business environment and recommended on how to maintain the sustainability of the telecommunication industries in Indonesia.